2016
DOI: 10.1371/journal.pone.0158434
|View full text |Cite
|
Sign up to set email alerts
|

It All Starts with a Sandwich: Identification of Sialidases with Trans-Glycosylation Activity

Abstract: Sialidases (3.2.1.18) may exhibit trans-sialidase activity to catalyze sialylation of lactose if the active site topology is congruent with that of the Trypanosoma cruzi trans-sialidase (EC 2.4.1.-). The present work was undertaken to test the hypothesis that a particular aromatic sandwich structure of two amino acids proximal to the active site of the T. cruzi trans-sialidase infers trans-sialidase activity. On this basis, four enzymes with putative trans-sialidase activity were identified through an iterativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
(52 reference statements)
3
13
0
Order By: Relevance
“…As hypothesized above, XyG accessibility may be limited for TmαFuc by the loop structure at the entrance to its active site ( Figure S3g). As previously shown for sialidases, transglycosylation activity is not only linked to how open the active site binding pocket is, but also to specific interactions inside or near the active site [48]. Indeed, in the current work both donor and acceptor specificities of each α-L-fucosidase seem to influence their transfucosylation potential significantly.…”
Section: Fgfco1 Catalysed Formation Of 2'fl Reaching a Molar Yield Basupporting
confidence: 64%
“…As hypothesized above, XyG accessibility may be limited for TmαFuc by the loop structure at the entrance to its active site ( Figure S3g). As previously shown for sialidases, transglycosylation activity is not only linked to how open the active site binding pocket is, but also to specific interactions inside or near the active site [48]. Indeed, in the current work both donor and acceptor specificities of each α-L-fucosidase seem to influence their transfucosylation potential significantly.…”
Section: Fgfco1 Catalysed Formation Of 2'fl Reaching a Molar Yield Basupporting
confidence: 64%
“…We observed that the total transglycosylation to hydrolysis (TG/HT) product ratio for the CelE-E316G-CBM3a construct was 40 to 140-fold higher than the values obtained for the control wild-type enzymes. Clearly our chimeric mutant is a highly efficient transglycosidase based on TG/HT metrics established for other CAZyme systems (Lundemo et al, 2013;Nordvang et al, 2016). Previous studies on another glucosidase have reported similar order of magnitude (70-fold) increase in TG/HT ratio but only after extensive mutagenesis and directed evolution of the wild-type enzymes (Kone et al, 2008), which further highlights the advantages offered by our current approach.…”
Section: Discussionsupporting
confidence: 52%
“…The binding pockets of HEX1 GTDDA and HEX1 GTEPG were much more shielded by the Trp residues than that of HEX1, so that the intermediate might be more protected against water molecules and, therefore, also against hydrolysis. The importance of such aromatic residues leading to a narrow substrate‐binding site for transglycosidase activity was also described for a GH33 sialidase …”
Section: Resultsmentioning
confidence: 96%